Research of methanogenesis waste waters of primary winemaking - Крусир, Галина Всеволодовна; Дубровин, Валерий Александрович; Полищук, Виктор Николаевич; Дубовик, Алексей Александрович; Соколова, Ирина Федоровна (Eastern-European Journal of Enterprise Technologies, 2014)
The present work provides an overview on the issues of analysis of wastewater of the primary winemaking enterprises. A comprehensive study on the wastewater’s chemical composition is provided aiming to select the optimal method of wastewater’s treatment. The chemical composition of wastewater is characterized by significant BOD (5.6 Zr02/1) and COD (9.1 Zr02/1). On the basis of the results of the research of chemical composition of the wastewater a method of anaerobic digestion in a reactor is proposed, as the most effective method of purification of wastewater, with the possibility of production of biogas and organic fertilizers. The essence of this method is the decomposition of organic substances without access of oxygen, by means of microorganisms, that are propelled to use carbon, constituting a part of organic molecule, or C02, as the electron acceptor. As a result, the organic substances in the waste liquid are transformed into biogas. The comparative analysis of existing reactors intended for fermentation of wastewater, used in the fermentation industries, was performed. On the basis of the above characteristics the UASB-reactor was selected. The optimal process parameters of anaerobic digestion of wastewater are studied and, according to the results, the optimum ambient temperature in the bioreactor is 40 °C. pH 7.4, the ratio of C: N=1:0,1, fermentation time made 4 days. On the basis of these results, the process flow diagram of wastewater treatment is proposed.